2005
DOI: 10.1016/j.orthres.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Cytological properties of stromal cells derived from giant cell tumor of bone (GCTSC) which can induce osteoclast formation of human blood monocytes without cell to cell contact

Abstract: When human blood monocytes were cocultured with stromal cells derived from human giant cell tumor of bone (GCTSC) and a Millipore filter (0.4 pm) was interposed between monocytes and GCTSC, multinucleated giant cell formation of monocytes was induced. The multinucleated giant cells have characters as osteoclast-like cells, indicating that a soluble osteoclast-inducing factor(s) is secreted from GCTSC expressing RANK, RANKL/ODF/OPGL and TACE mRNA. Furthermore, OCIF/OPG inhibited GCTSC-induced osteoclastogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
4
38
0
Order By: Relevance
“…This supposition is supported by the gene expression of additional markers of an early osteoblastic differentiation (e.g. collagen I, bone sialoprotein, and osteonectin) and the ability to differentiate osteoblasts (Cbfa-1, osterix, osteocalcin) under cell culture conditions [16,33,36]. A hypothesis is based on this fact that the neoplastic cells of the giant cell tumour (GCTSC) are derived histogenetically from osteoblastic cells.…”
Section: Differentiation Level Of the Neoplastic Stromal Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…This supposition is supported by the gene expression of additional markers of an early osteoblastic differentiation (e.g. collagen I, bone sialoprotein, and osteonectin) and the ability to differentiate osteoblasts (Cbfa-1, osterix, osteocalcin) under cell culture conditions [16,33,36]. A hypothesis is based on this fact that the neoplastic cells of the giant cell tumour (GCTSC) are derived histogenetically from osteoblastic cells.…”
Section: Differentiation Level Of the Neoplastic Stromal Cellsmentioning
confidence: 96%
“…In contrast, RANKL is expressed by the neoplastic GCTSC promoting the fusion of MNHC to MNGC, with macrophage colony-stimulating factor (M-CSF) acting as a co-factor [1,2,15]. Cell culture experiments have revealed that giant cell formation takes place even in the absence of any direct cell contact between GCTSC and MNHC [36]. In contrast, all three cell types of the GCT express the antagonistic ligand OPG [15].…”
Section: Functional Connections Between the Neoplastic And Non-neoplamentioning
confidence: 99%
“…Histologically, GCTB is composed of sheets of neoplastic ovoid mononuclear cells with high RANK ligand (RANKL) expression, RANK-positive mononuclear cells of myeloid linage, and a randomly distributed population of large RANKexpressing osteoclast-like giant cells (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Many researchers have shown that the giant cell of GCTB is osteoclastic in nature (4,6,10) and that the true neoplastic cells are ovoid cells displaying markers of mesenchymal stem cells that have partially differentiated along the osteoblast lineage (14)(15)(16)(17). These tumors are frequently described to contain small areas of osteoid matrix deposition, woven bone, and occasionally new bone, which may be reactive tissue at the tumor margin or formed de novo within the tumor (9,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The first is the mesenchymal stromal cell, which is of osteoblastic lineage as demonstrated by the expression of the osteoblastic markers osteopontin, osteocalcin, and osteonectin [5]. Furthermore, these cells are known to be the neoplastic element of the tumor, and they serve to regulate the tumor environment through the expression and secretion of the cytokine receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) [6]. In bone, RANKL acts in concert with M-CSF to promote the proliferation and differentiation of monocytes (of macrophage lineage) into osteoclast-like multinucleated giant cells [6].…”
Section: Introductionmentioning
confidence: 99%